The Royal Island - Pearl, Alexa, 1967- (Pearl, Alexa, 1967- Tales of Sasha, 2018)
Sasha, Kimani, and Wyatt are flying to the Royal Island, home of Sasha's parents, the King and Queen of flying horses, where Sasha hopes to meet her folks for the first time, but when they encounter a powerful storm that forces them to take shelter on a small island, Sasha's dream of finally seeing her parents is put in jeopardy.